Comparison of the effect of foot reflexology and body massage on physiological indicators and bilirubin levels in neonates under phototherapy - Zahra Jazayeri; Mahbobeh Sajadi; Hamid Dalvand; Mohammadreza Zolfaghari (Elsevier, 2021)
Background: Hyperbilirubinemia is one of the most common problems in infancy in the world. The aim of this study was to compare the effect of foot therapy and body massage on physiological indicators and bilirubin levels in infants under phototherapy. Methods: This study was a randomized clinical trial that conducted on 51 infants with jaundice at Imam Hussein Pediatrics' Medical Center, Goldis Hospital in Isfahan (Iran). The samples randomly assigned to first intervention (reflexology), second intervention (body massage) and control groups using the block randomization. In the reflexology group, the relevant area on each foot was massaged for 15 min in a relaxed position. In the massage body group, the limbs were massaged with circular motion. The massage was performed once a day for 15 min and the control group did not receive any intervention. Physiological indicators were monitored using vital sign monitoring tools, and blood bilirubin levels were measured photo metrically (intravenous blood samples from the wrist). Finally, the data were analyzed using descriptive and inferential statistics and SPSS software version 18. Results: The results showed that before the intervention there was no significant difference in the mean of physiological indicators and bilirubin level between the three groups (p > 0.05), but after the intervention the average percentage of arterial oxygen saturation and bilirubin levels were significantly improved in the intervention groups compared to the control group (p < 0.05), while the mean of heart rate and respiration rate between the three groups were not significant (p > 0.05). Conclusion: The results showed that reflexology and massage therapy can be effective in improving the condition of physiological indicators and blood bilirubin levels.